2022
DOI: 10.1021/acs.jmedchem.1c02186
|View full text |Cite
|
Sign up to set email alerts
|

Dithiocarbazate–FeIII, −CoIII, −NiII, and −ZnII Complexes: Design, Synthesis, Structure, and Anticancer Evaluation

Abstract: Non-platinum-metal complexes show great potential as anticancer agents. Herein, a series of dithiocarbazate non-Pt-metal complexes, including [FeIII(L)2]·Cl·2H2O 1, [CoIII(L)2]·NO3·2.5H2O 2, [NiII(L)2] 3, and [ZnII(L)2] 4, have been designed and evaluated for their efficacy as antineoplastic agents. Among them, complex 2 exhibited higher anticancer efficacy than complexes 1, 3, 4, and cisplatin against several cancer cell lines. Hemolysis assays revealed that complex 2 showed comparable hemolysis with cisplati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 78 publications
0
14
0
Order By: Relevance
“…Non-Pt metal compounds have been proposed as promising anticancer drugs to overcome cisplatin resistance. 41,42 On the basis of the properties of In( iii ) and thiosemicarbazones, In( iii ) 2-acetylpyridine thiosemicarbazone compounds were synthesized, and their anticancer activities were investigated (Table 1). The obtained results demonstrated that In( iii ) compounds exhibit remarkable anticancer activity.…”
Section: Discussionmentioning
confidence: 99%
“…Non-Pt metal compounds have been proposed as promising anticancer drugs to overcome cisplatin resistance. 41,42 On the basis of the properties of In( iii ) and thiosemicarbazones, In( iii ) 2-acetylpyridine thiosemicarbazone compounds were synthesized, and their anticancer activities were investigated (Table 1). The obtained results demonstrated that In( iii ) compounds exhibit remarkable anticancer activity.…”
Section: Discussionmentioning
confidence: 99%
“…Although platinum (Pt) drugs are considered to be the first-line chemotherapeutics in the clinic against various solid tumors, DNA-targeted Pt-based anticancer drugs not only have severe side effects and a lack of targeting but also are ineffective in inhibiting tumor metastasis. At present, to overcome the shortcomings of Pt drugs, one of the most promising strategy is to design non-Pt metal drugs based on other new anticancer mechanism(s) and then use carriers to improve their targeting ability and reduce their side effects in vivo . …”
Section: Introductionmentioning
confidence: 99%
“…Over the last years, the interest in the study of ONS donor ligands has increased significantly due to their ligation properties and potential applications of their transition metal complexes in pharmacology and medicine. , For example, 3-aminopyridine-2-carboxaldehyde thiosemicarbazone, well known as triapine, is one of the most extensively studied drugs and has been tested in nearly 30 clinical phases I/II trials as an antiproliferative agent . Likewise, di-2-pyridylketone-4-cyclohexyl-4-methyl-3-thiosemicarbazone (DpC-TSC) has also entered clinical phase I studies as a chemotherapeutic agent. , Out of this class of compounds, similar to thiosemicarbazones, S-substituted dithiocarbazates (DTCs) are also well known for their antitumor, antimicrobial, antifungal, and antibacterial activities. , ,,, Moreover, N ’-(phenyl-pyridin-2-yl-methylene)-hydrazine carbodithioic acid methyl ester (PHCM) was also found to enhance radiation-induced cell death of an NSCLC cell line, H460, both in vivo and in vitro . Interestingly, the possible use in bio-imaging and in the treatment of pancreatic cancer of a dithiocarbazate-copper complex has been recently published …”
Section: Introductionmentioning
confidence: 99%